非對稱原則：應對腦機介面技術的主體性風險: Asymmetry Principle: Managing the Subjective Risk of Brain-Computer Interface Technology - 韓丹 (International Journal of Chinese & Comparative Philosophy of Medicine, 2023)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. Based on the innovation of brain–computer interface technology and the development of application scenarios for brain–computer interfaces, Zhenming Zhai puts forward the “asymmetry principle” in his recent paper “Risk of Brain–Computer Interaction.” This principle can effectively control the risk of the subject to protect and maintain the subject status of the individual. This principle is a technical ethical requirement that must be respected when manually inputting information and signal.